The role of ixekizumab in non-radiographic axial spondyloarthritis - Bon San Koo; Tae-Hwan Kim (Therapeutic Advances in Musculoskeletal Disease, 2021)
Among patients with axial spondyloarthritis (axSpA), non-radiographic axial spondyloarthritis (nr-axSpA) is distinguished from ankylosing spondylitis (AS) by a lack of obvious radiographic changes in the sacroiliac joint. Tumor necrosis factor inhibitor (TNFi) has been used as a highly effective treatment in patients with AS and has shown good efficacy and safety in clinical trials in patients with nr-axSpA. As the pathophysiological mechanism for axSpA has started to become better recognized, various drugs other than TNFi, all of which are related to the interleukin-17 (IL-17) axis, are being evaluated in patients with axSpA. IL-17 inhibitors, such as secukinumab and ixekizumab, are effective drugs for patients with AS. A recent clinical trial reported that ixekizumab, a monoclonal antibody against IL-17A, was also effective in patients with nr-axSpA. In a COAST-X study, ixekizumab was superior to a placebo for improving signs and symptoms in patients with nr-axSpA at weeks 16 and 52. The adverse events were no different from those found in previous ixekizumab studies, and no new safety signals were identified. However, when considering several IL-17 inhibitors, it is necessary to obtain sufficient data to identify the exacerbation of extra-articular manifestation. In terms of effectiveness and safety, ixekizumab may be an appropriate alternative to TNFi in nr-axSpA patients.